2001
DOI: 10.1139/l01-043
|View full text |Cite
|
Sign up to set email alerts
|

The August 17, 1999, Kocaeli (Turkey) earthquake — damage to structures

Abstract: The 1975 Turkish code provisions are first reviewed to provide the background for design and detailing of structures prior to the earthquake. The performance of reinforced concrete and masonry structures is described indicating many of the deficiencies in design, detailing, and construction execution. The behaviour of precast concrete structures, steel structures, and industrial facilities is also presented. The provisions of the 1997 Turkish building code are summarized and a description of new construction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 0 publications
0
35
0
6
Order By: Relevance
“…Interestingly, it is documented that some of the asmolen buildings failed due to the weak vertical elements as compared to horizontal members (Aschheim et al 2000;Saatcioglu et al 2001). Reports also include the common deficiencies of RC buildings including the asmolen buildings.…”
Section: Reported Performance Of Asmolen Buildings In Earthquakes In mentioning
confidence: 99%
“…Interestingly, it is documented that some of the asmolen buildings failed due to the weak vertical elements as compared to horizontal members (Aschheim et al 2000;Saatcioglu et al 2001). Reports also include the common deficiencies of RC buildings including the asmolen buildings.…”
Section: Reported Performance Of Asmolen Buildings In Earthquakes In mentioning
confidence: 99%
“…Post-earthquake observations revealed that beamcolumn connections are widely influence the overall seismic response of precast concrete structures (Saatcioglu et al 2001;Ozden and Meydanli 2003;Senel and Palanci 2013). It is still a challenging subject to develop precast concrete beam-column connections emulating the seismic performance of monolithic systems to maintain advantages of precast construction process for multi-story buildings.…”
Section: Introductionmentioning
confidence: 99%
“…After August 1999 Kocaeli and November 1999 Düzce Earthquakes, site investigations revealed that structural damage and collapse of one-story precast structures were common Saatcioglu et al (2001), Ataköy (1999), Sezen et al (2000), Bruneau (2002), Sezen and Whittaker (2006). Various types of structural damage were frequently observed in one-story precast structures, such as flexural hinges at the base of the columns, axial movement of the roof girders that led to pounding against the supporting columns or falling of the roof girders, Fig.…”
Section: Introductionmentioning
confidence: 99%